Regulation and Gene Expression Profiling of NKG2D Positive Human Cytomegalovirus-Primed CD4(+) T-Cells - Jensen, Helle (Public Library of Science, 2012)
NKG2D is a stimulatory receptor expressed by natural killer (NK) cells, CD8(+) T-cells, and γδ T-cells. NKG2D expression is normally absent from CD4(+) T-cells, however recently a subset of NKG2D(+) CD4(+) T-cells has been found, which is specific for human cytomegalovirus (HCMV). This particular subset of HCMV-specific NKG2D(+) CD4(+) T-cells possesses effector-like functions, thus resembling the subsets of NKG2D(+) CD4(+) T-cells found in other chronic inflammations. However, the precise mechanism leading to NKG2D expression on HCMV-specific CD4(+) T-cells is currently not known. In this study we used genome-wide analysis of individual genes and gene set enrichment analysis (GSEA) to investigate the gene expression profile of NKG2D(+) CD4(+) T-cells, generated from HCMV-primed CD4(+) T-cells. We show that the HCMV-primed NKG2D(+) CD4(+) T-cells possess a higher differentiated phenotype than the NKG2D(–) CD4(+) T-cells, both at the gene expression profile and cytokine profile. The ability to express NKG2D at the cell surface was primarily determined by the activation or differentiation status of the CD4(+) T-cells and not by the antigen presenting cells. We observed a correlation between CD94 and NKG2D expression in the CD4(+) T-cells following HCMV stimulation. However, knock-down of CD94 did not affect NKG2D cell surface expression or signaling. In addition, we show that NKG2D is recycled at the cell surface of activated CD4(+) T-cells, whereas it is produced de novo in resting CD4(+) T-cells. These findings provide novel information about the gene expression profile of HCMV-primed NKG2D(+) CD4(+) T-cells, as well as the mechanisms regulating NKG2D cell surface expression.